The pathophysiological changes associated with neonatal death of cloned pigs. Issue 2 (August 2020) - Ao, Zheng; Gu, Ting; Zhao, Huaxing; Shi, Junsong; Zheng, Enqin; Cai, Gengyuan; Wu, Zhenfang; Li, Zicong
Abstract : Cloned pigs generated by the somatic cell transfer nuclear (SCNT) technique are highly valuable for agriculture, biomedicine, and life sciences. However, the neonatal mortality rate of cloned pigs is very high. The reasons causing the massive loss of cloned pigs during their neonatal ages are unclear. In the present study, we found that the neonatal death of cloned pigs was associated with aberrant purine metabolism, impaired renal morphology and function, and decreased hepatic Hprt1 expression. The downregulation of Hprt1, a key purine metabolism regulation gene, in the liver was responsible for the elevation of an important purine metabolite, uric acid, in the serum, causing abnormalities in kidney morphology and function and leading to death of neonatal cloned pigs. This study provided insights into the pathophysiological mechanisms underlying the neonatal death of clone pigs, and results will help improve their survival rate.